1915 N.D. Laws 225 - (:unkn) unknown (My University, 1915)
Ch. 161, § 67: Prohibited noncitizens from owning or possessing any shotgun or rifle; violators subject to fine, imprisonment, confiscation of weapon.
Keywords: POSSESSION - DANGEROUS PERSONS